Solve for y (y-5)-(y+4)=2y

Math
(y-5)-(y+4)=2y
Simplify (y-5)-(y+4).
Tap for more steps…
Simplify each term.
Tap for more steps…
Apply the distributive property.
y-5-y-1⋅4=2y
Multiply -1 by 4.
y-5-y-4=2y
y-5-y-4=2y
Simplify by adding terms.
Tap for more steps…
Combine the opposite terms in y-5-y-4.
Tap for more steps…
Subtract y from y.
0-5-4=2y
Subtract 5 from 0.
-5-4=2y
-5-4=2y
Subtract 4 from -5.
-9=2y
-9=2y
-9=2y
Since y is on the right side of the equation, switch the sides so it is on the left side of the equation.
2y=-9
Divide each term by 2 and simplify.
Tap for more steps…
Divide each term in 2y=-9 by 2.
2y2=-92
Cancel the common factor of 2.
Tap for more steps…
Cancel the common factor.
2y2=-92
Divide y by 1.
y=-92
y=-92
Move the negative in front of the fraction.
y=-92
y=-92
The result can be shown in multiple forms.
Exact Form:
y=-92
Decimal Form:
y=-4.5
Mixed Number Form:
y=-412
Solve for y (y-5)-(y+4)=2y

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top